Modern approaches to the assessment of the cost of commercial bank - Natal’ya I. Malykh; Natal’ya A. Prodanova (Статистика и экономика)
Financial analysis and assessment of the company’s activity in the market economy plays an important role as an indicator of the organization reliability and its competitiveness. For a commercial bank, a positive opinion on its financial position becomes even more important as not only the effectiveness of the bank’s operation, but also its clients interest depend on the degree of the bank’s reliability.A comprehensive activity assessment of a commercial bank in addition to financial analysis is the analysis of risks, strengths and weaknesses of the bank and the business valuation of a commercial bank. Business valuation – topical areas of financial management, and eventually its importance will only increase.Financial institution should be regarded not only from the view of financial statements as an entity, but also from the view of the investment attractiveness as a business unit for a comprehensive idea of its activity.The economic activity of the banking sector is considered by the authors as an operating business unit – bank. The article considers the modern approaches to the valuation of a commercial bank, the necessity of taking into account the specifics of banking activities in the evaluation, the difficulties of assessment, typical for the financial services’ sector.The authors note that the business valuation of a commercial bank shall apply a single method: estimate the cost of equity capital (and not the company, as it is customary in order to apply standard accounting rules), and use only cash flows that could be traced – dividends.For the purposes of evaluating the absolute value of the bank it can be applied the model of discounted dividends, provided that only equity will play the role of capital, and cash flows, except for the dividend, can be omitted (due to the complexity of the calculation).In comparison with non-financial enterprises, some of multipliers for comparative approach to evaluation cannot be adequately applied to banks. To assess financial institutions using the comparative method, it can be mainly used the multipliers based on the value of own capital – the ratio «price/earnings» (PE), and the ratio of «price/book value» (PBV).The authors emphasize that the evaluation of the market value of the business or assets is needed today not only in the framework of transactions of sale and purchase or in determining of the collateral value of the object, but also to make competent strategic and management decisions.A comprehensive analysis determines the competitiveness, reliability and attractiveness of the bank for the customer and for the investor.Thus, after analyzing the financial situation of any bank, with a considerable degree of confidence among banks-counterparts we can choose the most attractive and ensure its reliability, a further operation and for the bank’s customers, feeling more safe in cash transferring for the management and effectiveness of services.